A novel nomogram containing efficacy indicators to predict axillary pathologic complete response after neoadjuvant systemic therapy in breast cancer - Shi, Wenjie; Huang, Xiaofeng; Wang, Ye; Wan, Xinyu; He, Jinzhi; Xu, Yinggang; Zhang, Weiwei; Chen, Rui; Xu, Lu; Zha, Xiaoming; Wang, Jue (Frontiers in Endocrinology, 2022)
Background: Neoadjuvant systemic therapy (NST) could make some clinically node-positive (cN+) breast cancer patients achieve axillary pathologic complete response (pCR). This study aimed to identify the patients who are likely to achieve axillary pCR and help surgeons make surgical decisions on the axilla. Methods: The cN+ breast cancer patients who received NST from 2015 to 2021 at The First Affiliated Hospital of Nanjing Medical University were enrolled. Univariate and multivariate logistic regression analyses were performed, and a nomogram was constructed based on the results of multivariate logistic regression analysis to predict the probability of axillary pCR and validated. Results: The axillary pCR was achieved in 208 (38.7%) patients. Patients who had a higher radiological response rate of breast tumor (P = 0.039), smaller longest diameter of positive node after NST (P = 0.028), ER-negative status (P = 0.006), HER2-positive status (P = 0.048) and breast pCR (P < 0.001) were more likely to achieve axillary pCR. The nomogram had an area under the receiver operating characteristic curve (AUC) of 0.795 (95% CI: 0.747–0.843), and the calibration curve showed good agreement. Conclusion: A nomogram was constructed to predict the axillary pCR of cN+ patients receiving NST based on baseline and efficacy indicators to assist surgeons in making surgical decisions on the axilla.